2013
DOI: 10.1088/1751-8113/46/7/075001
|View full text |Cite
|
Sign up to set email alerts
|

Transfer matrix computation of critical polynomials for two-dimensional Potts models

Abstract: Abstract.In our previous work [1] we have shown that critical manifolds of the q-state Potts model can be studied by means of a graph polynomial P B (q, v), henceforth referred to as the critical polynomial. This polynomial may be defined on any periodic twodimensional lattice. It depends on a finite subgraph B, called the basis, and the manner in which B is tiled to construct the lattice. The real roots v = e K − 1 of P B (q, v) either give the exact critical points for the lattice, or provide approximations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
109
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 28 publications
(118 citation statements)
references
References 42 publications
(215 reference statements)
9
109
0
Order By: Relevance
“…seven) quadrangulations of self-dual (resp. non-self-dual) type using several complementary techniques: MC simulations, TM computations, and the method of critical polynomials (CP) [28,35,36,70,71]. These numerical results agree, without exception, with conjecture 1.1.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…seven) quadrangulations of self-dual (resp. non-self-dual) type using several complementary techniques: MC simulations, TM computations, and the method of critical polynomials (CP) [28,35,36,70,71]. These numerical results agree, without exception, with conjecture 1.1.…”
Section: Introductionsupporting
confidence: 58%
“…The location of the phase transitions for the quadrangulations in figures 2 and 3 can also be studied by the method of critical polynomials [28,35,36,70,71]. These polynomials P B (q, v) can in principle be computed for any lattice generated by the tessellation of the plane by some finite basis B.…”
Section: Critical Polynomialsmentioning
confidence: 99%
“…The existence of the BK phase has been verified for all Archimedean lattices in [39,40], and its extent in the (Q, v) plane has been accurately estimated. It was found that in most, but not all [38], cases Q c = 4.…”
Section: The Berker-kadanoff Phasementioning
confidence: 77%
“…In addition to the interesting open problems related to the critical polynomial method, it is yet to be determined how widely applicable it is. The definition (3) is easily generalized to the Q-state Potts model and gives excellent estimates for any Q [31,40], even in the imaginary temperature regime [41]. The eigenvalue method presented here was also adapted to compute the growth constant of self-avoiding walks and was able finally to rule out a longstanding conjecture [39].…”
mentioning
confidence: 99%